Mapping 15 years of crayfish plague in the Iberian Peninsula: The impact of two invasive species on the endangered native crayfish. - Laura Martín-Torrijos (Public Library of Science (PLoS), 2019)
Crayfish plague, caused by the pathogen Aphanomyces astaci, is one of the main factors responsible for the decimation of the native European crayfish species Austropotamobius pallipes. In Spain, two North American freshwater crayfish species, Procambarus clarkii and Pacifastacus leniusculus, were intentionally introduced during the 1970s for aquaculture and fishery purposes. Since then, incidences of crayfish plague have been continually reported. In this work, we evaluated more than 50 diagnosed cases of crayfish plague that have occurred in the Iberian Peninsula since 2004 by performing a microscopic examination of infected specimens and by molecularly identifying and haplotyping the pathogen. Our results showed that (i) the pathogen A. astaci has been active 45 years since the first introductions of the invasive North American crayfish species in the Iberian Peninsula, and (ii) P. clarkii and P. leniusculus are chronic reservoirs of the crayfish plague pathogen. Moreover, our data confirmed a correspondence between pathogen origin and spread and the specific haplotypes carried by the North American invasive crayfish located in the vicinity of each outbreak. We generated a crayfish plague incidence map of the Iberian Peninsula that shows (i) a northern area, mainly inhabited by alien P. leniusculus, where crayfish plague cases are associated with the b-haplotype specific to P. leniusculus, and (ii) southern, central and eastern areas that are basically inhabited by alien P. clarkii, where crayfish plague cases are associated with the d1- and d2-haplotypes specific to P. clarkii. The results presented here are evidence of the long standing and negative impact of the two invasive crayfish species on the native species, indicating the need for more extensive control measures.